2017
DOI: 10.1111/ppc.12206
|View full text |Cite
|
Sign up to set email alerts
|

Memory Impairment Following Electroconvulsive Therapy in Chinese Patients with Schizophrenia: Meta-Analysis of Randomized Controlled Trials

Abstract: The ECT-AP combination was associated with greater transient memory impairment compared to AP monotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…For other noninvasive brain stimulations, such as transcranial direct current stimulation (tDCS) (42)(43)(44) and electroconvulsive therapy (45,46), another objective is to monitor the cognitive effects of rTMS. Consistent with previous meta-analyses focusing on adult patients with MDD (47,48), this systematic review also found that a therapeutic rTMS course for child and adolescent patients with FEDN MDD may produce modest cognitive enhancing effects.…”
Section: Discussionmentioning
confidence: 99%
“…For other noninvasive brain stimulations, such as transcranial direct current stimulation (tDCS) (42)(43)(44) and electroconvulsive therapy (45,46), another objective is to monitor the cognitive effects of rTMS. Consistent with previous meta-analyses focusing on adult patients with MDD (47,48), this systematic review also found that a therapeutic rTMS course for child and adolescent patients with FEDN MDD may produce modest cognitive enhancing effects.…”
Section: Discussionmentioning
confidence: 99%
“…Despite clear evidence of the symptomatic effectiveness of ECT in patients with schizophrenia, there remains a controversy on the cognitive side effects of ECT. Although randomised controlled trials have suggested greater transient memory impairment in treatments of ECT combined with antipsychotics when compared with antipsychotic monotherapy for Chinese patients with schizophrenia, 16,34 ECT-induced acute cognitive impairments typically resolved within several weeks after the last ECT session. 35,36 Our results is in agreement with recent studies demonstrating cognitive improvement after ECT in patients with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Recent efforts to further reduce cognitive side effects focus on changing from brief to ultra brief pulse stimulation[45]. While a few individual testimonies reported longlasting and severe memory disturbances after ECT[46], extensive psychological tests could not detect significant memory deficits beyond six months following a course of ECT[47].…”
Section: Place Of Electroconvulsive Therapy In Modern Psychiatrymentioning
confidence: 99%